Aid effectiveness: when aid spurs investment. Issue 87 (17th May 2021) - Nowak-Lehmann, Felicitas; Gross, Elena
Abstract : Purpose: This paper aims to analyze the effectiveness of aid in stimulating investment using different measures of aid and up-to-date panel time-series techniques. This study controls for endogeneity by using dynamic ordinary least squares (DOLS) and minimizes the risk of running a spurious long-run relationship by using series that are cointegrated. This paper finds evidence that aid promotes investment in countries with good institutional quality and gain interesting insights on the influence of country characteristics and the amount of aid received. Aid is ineffective in countries with unfavorable country characteristics such as a colonial past, being landlocked and with large distances to markets. Aid can boost investment in regions that receive high (above-median) amounts of aid such as Africa and the Middle East but not in regions that receive low amounts of aid. Investment-targeted aid is effective but non-investment-related aid can also enhance investment. Design/methodology/approach: Regressions on the aid-investment nexus are based on either a rather simple (115 countries) or an extended/augmented investment model (91 countries). The data covers the period of 1973–2011 and 1985–2011 if the institutional quality is included. This study estimates the relationship between aid and investment by applying the DOLS/dynamic feasible generalized least squares technique which is based on a long-run relationship of the regression variables (cointegration). In this framework, this paper incorporates country-fixed effects, control for endogeneity, autocorrelation and take heteroscedasticity and cross-country correlation of the residuals into account. Findings: This study finds empirical evidence that aid promotes investment in countries with good institutional quality and gain interesting insights on the role played by country characteristics and the amount of aid received. Aid is ineffective in countries with unfavorable country characteristics such as the colonial past, being landlocked, distant from markets. Aid can boost investment in regions that receive high (above-median) amounts of aid such as Africa and the Middle East. Investment-targeted aid is effective but non-investment-related aid also able to enhance investment. Research limitations/implications: The study looks at the investment to gross domestic product (GDP) ratio (including domestic investment and foreign direct investment (FDI)) and, hence does not disentangle these factors. It looks at the net effect (positive and negative impact together) and, therefore does not allow to identify the direct crowding out the impact of aid. Of course, if this paper finds that aid has a negative impact on investment, it is clear that aid must have crowded out either domestic investment or FDI or both. Practical implications: The authors think that it is relevant to have identified the circumstances and settings in which foreign aid can be particularly effective and in which foreign aid needs accompanying measures that improve the effectiveness of aid. Also, it is relevant that the relative amount of aid received (aid-to-GDP ratio) must be quite high so that aid can increase investment. Social implications: This study sees that the least developed, low-income countries and (in terms of regions) the sub-Saharan Africa countries benefit from aid. This is very desirable. This paper further sees that higher relative amounts of aid do help more and that it is helpful to care about a better institutional quality in developing countries. Hence, this study provides some support for the desirability of aid. Originality/value: The paper was done very diligently, and this study is very confident that the results are robust. This paper is also confident that this study has studied the long-run (which is of special importance) nexus between aid and investment. The estimation technique used is original, as it combines regular DOLS with corrections for autocorrelation and cross-section dependence.